Managerial conservatism, board independence and corporate innovation - Lu, Jun; Wang, Wei (Journal of Corporate Finance, 2018)
Using panel data on U.S. public firms, we document a positive effect of board independence on corporate innovation. This effect is concentrated in firms that are larger in size, in the non-technical industries, facing less product market competition, and using more debt, where managers are more likely to be excessively risk averse. We establish causality of board independence on innovation using a difference-in-difference approach that exploits an exogenous shock to board composition, namely, the mandate of a majority of outside directors on company boards by NYSE and NASDAQ in response to the passage of Sarbanes-Oxley Act in 2002. We further examine incentive compensation as a possible mechanism. We show that firms with more independent boards use more equity-based compensation, especially stock options, to promote managerial risk-taking.